2019
DOI: 10.1103/physrevlett.123.043401
|View full text |Cite
|
Sign up to set email alerts
|

Stereodynamical Control of a Quantum Scattering Resonance in Cold Molecular Collisions

Abstract: Cold collisions of light molecules are often dominated by a single partial wave resonance. For the rotational quenching of HD(v = 1, j = 2) by collisions with ground state para-H2, the process is dominated by a single L = 2 partial wave resonance centered around 0.1 K. Here, we show that this resonance can be switched on or off simply by appropriate alignment of the HD rotational angular momentum relative to the initial velocity vector, thereby enabling complete control of the collision outcome.arXiv:1905.0476… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
77
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 48 publications
(78 citation statements)
references
References 63 publications
1
77
0
Order By: Relevance
“…18 Observations of resonances in other high-resolution experiments of molecular interactions, including in vibrational excitation studies, 8,11 have demonstrated similar sensitivities to the corresponding calculated energy levels and PESs. [5][6][7]9,14,29 In addition to probing the local energy landscape via dynamical resonances, initial alignment 23,[30][31][32][33][34][35][36][37][38] or orientation [39][40][41][42][43][44] of selected reactant quantum states can be used to gauge the geometric preferences and uncover the associated reaction pathways of molecular encounters. 37,38 In this case, specific portions of the PES can be explored selectively by confining the relative geometry of the interacting species.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…18 Observations of resonances in other high-resolution experiments of molecular interactions, including in vibrational excitation studies, 8,11 have demonstrated similar sensitivities to the corresponding calculated energy levels and PESs. [5][6][7]9,14,29 In addition to probing the local energy landscape via dynamical resonances, initial alignment 23,[30][31][32][33][34][35][36][37][38] or orientation [39][40][41][42][43][44] of selected reactant quantum states can be used to gauge the geometric preferences and uncover the associated reaction pathways of molecular encounters. 37,38 In this case, specific portions of the PES can be explored selectively by confining the relative geometry of the interacting species.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7]9,14,29 In addition to probing the local energy landscape via dynamical resonances, initial alignment 23,[30][31][32][33][34][35][36][37][38] or orientation [39][40][41][42][43][44] of selected reactant quantum states can be used to gauge the geometric preferences and uncover the associated reaction pathways of molecular encounters. 37,38 In this case, specific portions of the PES can be explored selectively by confining the relative geometry of the interacting species. Spatial alignment (alignment parallel or perpendicular to a reference axis) through polarized laser light has revealed pronounced preferences for specific initial configurations, 30,[33][34][35][36][37][38] and even enabled the three-dimensional visualization of distinct microscopic reaction pathways.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the low collision energies, E coll , typical of orbiting resonances, the number of partial waves implied in the dynamics is relatively small and this circumstance facilitates the performance of precise fundamental calculations, as a consequence there is a growing interest, both experimental and theoretical, in the stereodynamics of collisions in this low E coll range. [19][20][21][22][23][24][25][26] The pioneering work of Balakrishnan and Dalgarno [27] on reactivity at ultra-low temperatures was performed for the F + H 2 system and, at temperatures down to a few K, the reaction is also of interest in astrophysics, where the HF molecule is used to estimate the depletion of fluorine from ice mantles in dense clouds, and as a tracer of H 2 in the diffuse interstellar medium [28,29]. This reaction, which has been a prototype in the field of reaction dynamics since the seventies, is very well known in many respects.…”
Section: Introductionmentioning
confidence: 99%
“…We consider the inelastic scattering problem of two diatomic molecules prepared in a wide range of internal quantum states and undergoing collisions over a wide range of collision energies. Accurate predictions of probabilities for such collisions are required for applications in astrophysics [4], planetary atmosphere models, the development of new crossed-beam experiments for precision measurements [5], cold chemistry [6,7], as well as the mechanistic understanding of microscopic collision dynamics [8,9]. Rigorous quantum calculations of inelastic molecule-molecule scattering must be performed in six nuclear dimensions and account for all couplings between the internal and translational motion states of the molecules.…”
mentioning
confidence: 99%